Crowdtruth validation: a new paradigm for validating algorithms that rely on image correspondences - Maier-Hein, Lena; Kondermann, Daniel; Roß, Tobias; Mersmann, Sven; Heim, Eric; Bodenstedt, Sebastian; Kenngott, Hannes Götz; Sancez Bach, Alexandro; Wagner, Martin; Preukschas, Anas; Wekerle, Anna-Laura; Helfert, Stefanie; et al. (International journal of computer assisted radiology and surgery, 2015)
Feature tracking and 3D surface reconstruction are key enabling techniques to computer-assisted minimally invasive surgery. One of the major bottlenecks related to training and validation of new algorithms is the lack of large amounts of annotated images that fully capture the wide range of anatomical/scene variance in clinical practice. To address this issue, we propose a novel approach to obtaining large numbers of high-quality reference image annotations at low cost in an extremely short period of time.